Molecular characterization of Adenovirus circulating in Central and South america durin 2006-2008 period (2009)
ABSTRACT: Background Human Adenoviruses are recognized pathogens, causing a broad spectrum of diseases. Serotype identification is critical for epidemiological surveillance, detection of new strains and understanding of HAdvs pathogenesis. Little data is available about HAdvs subtypes in Latin America. Methods In this study, we have molecularly characterized 213 adenoviruses collected from ILI presenting patients, during 2006-08, in Central and South America. Results Our results indicate that 161(76%) adenoviruses belong to subgroup C, 45 (21%) to subgroup B and 7 (3%) to subtype E4.